The Association Between Smoke-Free School Policies and Adolescents’ Perceived Antismoking Norms: Moderation by School Connectedness - Schreuders, Michael (Nicotine Tob Res, 2019)
INTRODUCTION: Many European schools implement smoke-free school policies (SFSPs). SFSPs may decrease adolescent smoking by causing adolescents to perceive stronger antismoking norms, yet there exists no quantitative evidence that indicates for which norms and for whom such effects may occur. This study therefore assessed to what extent adolescents’ perceived antismoking norms among best friends, teachers, and society at large were associated with SFSPs, and whether these associations were moderated by adolescents’ level of school connectedness. AIMS AND METHODS: Survey data were collected in 2016/2017 on 10,653 adolescents aged 14–16 years old and 315 staff members in 55 schools from seven European cities. Associations of adolescent-perceived SFSPs and staff-reported SFSPs with best friend, teacher, and societal antismoking norms were estimated in multilevel logistic regression models, adjusted for demographics and school-level smoking prevalence. We tested for interaction between school connectedness and SFSPs. RESULTS: Adolescent-perceived SFSPs were positively associated with antismoking norms by teachers (odds ratio [OR]: 1.46, 95% confidence interval [CI]: 1.15–1.85), were negatively associated with antismoking norms by best friends (OR: 0.81, 95% CI: 0.67–0.99), but were not significantly associated with antismoking norms by society at large (OR: 0.87, 95% CI: 0.74–1.02). All interaction tests between adolescent-perceived SFSPs and school connectedness were nonsignificant. Staff-reported SFSPs were not associated with any norm and showed no significant interaction with school connectedness. CONCLUSIONS: We found that SFSPs are associated with adolescents’ perception of more antismoking norms by teachers, but less antismoking norms by best friends, irrespective of adolescents’ level of school connectedness. IMPLICATIONS: Smoke-free school policies, just as many other tobacco control policies, are assumed to foster adolescents’ perception of antismoking norms. Still, current evidence does not demonstrate which antismoking norms may be influenced by SFSPs and whether this influence is equal for adolescents with different levels of school connectedness. This study suggests that SFSPs foster adolescents’ perception of antismoking norms by teachers, but may concurrently lead to the perception of less antismoking norms by best friends, irrespective of adolescents’ school connectedness. SFSPs may therefore need to be complemented with interventions that target antismoking norms in adolescent peer groups.